Peran Dinas Pendidikan dan Kebudayaan Provinsi Jawa Tengah dalam Pengembangan Sekolah Luar Biasa (SLB) di Semarang - Paristiawan, Made Febriantha; Taufiq, Achmad; ., Purwoko (Journal of Politic and Government Studies, 2017)
This study is motivated by the increasing or the number of Children with Special Needs, so also the number of SLB that has been established in almost every regency / city. From the above statement it does not make the role of the Department of Education and Culture of Central Java province is completed, because the problem of education in SLB is not only related to the quantity but also the quality. This means that the Office of Education and Culture of Central Java Province should also have a role in improving the quality of education in SLB Negeri and private SLB as an effort to improve quality in public schools so that SLB graduate students can also have good quality. This research has purpose to know the role of Department of Education and Culture of Central Java Province in the way to develop SLB in Semarang.Â The type of research used in this study is qualitative research method using an analytical descriptive approach that describes the actual situation occurs and create a systematic, factual and accurate description of the facts, properties and relationships between the phenomena investigated. Methods of data collection in research using observation method, documentation and open interview. In this study the data that have been collected will be analyzed and then drawing conclusions.Â The results of this study found that the Role of Education and Culture Office of Central Java Province in the development of SLB in Semarang is as a policymaker, coordinating, coaching and supervising as well as compiling learning programs based on the curriculum used is K-13 curriculum, In accordance with government regulations for special needs schools. Programs planned and to be delivered must contain 5 aspects to be conveyed. The five aspects are: 1) Games, 2) rhythmic activities, 3) development activities of religious self-test, 4) physical fitness activity, and 5) health, the five aspects are developed into standard competence and basic competence.Â